Calmodulin 1 Regulates Senescence and ABA Response in Arabidopsis - Dai, Cheng; Lee, Yuree; Lee, In C.; Nam, Hong G.; Kwak, June M. (Frontiers in Plant Science, 2018)
Cellular calcium acts as a second messenger and regulates diverse developmental events and stress responses. Cytosolic calcium has long been considered as an important regulator of senescence, however, the role of Ca2+ in plant senescence has remained elusive. Here we show that the Calmodulin 1 (CaM1) gene, which encodes Ca2+-binding protein calmodulin1, positively regulates leaf senescence in Arabidopsis. Yellowing of leaves, accumulation of reactive oxygen species (ROS), and expression of the senescence-associated gene 12 (SAG12) were significantly enhanced in CaM1overexpression plants. In contrast, abscisic acid (ABA)-triggered ROS production and stomatal closure were reduced in amiRNA-CaM1 plants. We found a positive-feedback regulation loop among three signaling components, CaM1, RPK1, and RbohF, which physically associate with each other. RPK1 positively regulates the expression of the CaM1 gene, and the CaM1 protein, in turn, up-regulates RbohF gene expression. Interestingly, the expression of CaM1 was down-regulated in rbohD, rbohF, and rbohD/F mutants. We show that CaM1 positively regulates ROS production, leaf senescence, and ABA response in Arabidopsis.